2019
DOI: 10.3389/fgene.2019.01101
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Loss Does Not Always Entail Negative Genetic Consequences

Abstract: Although habitat loss has large, consistently negative effects on biodiversity, its genetic consequences are not yet fully understood. This is because measuring the genetic consequences of habitat loss requires accounting for major methodological limitations like the confounding effect of habitat fragmentation, historical processes underpinning genetic differentiation, time-lags between the onset of disturbances and genetic outcomes, and the need for large numbers of samples, genetic markers, and replicated la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…We used flow cytometry to estimate haploid genome size in both (Yang et al, 2010) and pairwise geographic distance, as in (Carvalho et al, 2019).…”
Section: Genome Size Estimation Dna Extraction Genotype-by-sequenmentioning
confidence: 99%
“…We used flow cytometry to estimate haploid genome size in both (Yang et al, 2010) and pairwise geographic distance, as in (Carvalho et al, 2019).…”
Section: Genome Size Estimation Dna Extraction Genotype-by-sequenmentioning
confidence: 99%
“…Impacts of fragmentation and habitat loss on plant genetic diversity are still poorly understood, despite the increase in the number of studies in recent years ( Storfer et al, 2010 ; Manel and Holderegger, 2013 ). Several works point out the decreasing in genetic diversity due to fragmentation process (e.g., Jump and Peñuelas, 2006 ; Aparicio et al, 2012 ; Carvalho et al, 2015 ; Gómez-Fernández et al, 2016 ; Collevatti et al, 2020a ), while others found no reduction in genetic diversity (e.g., Hall et al, 1996 ; Collevatti et al, 2001 ; Bacles et al, 2005 ; Winkler et al, 2011 ; Carvalho et al, 2019 ; Soares et al, 2019 ). The variation in fragmentation and habitat loss effects on genetic diversity may be due to differences in life history because each species respond to landscape changes according to their dispersal capacity and ecological requirements ( Prevedello and Vieira, 2010 ; Eycott et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Movement is modulated by the quality of the intervening habitat matrix (Renjifo, 2001), the size and distribution of remnant habitat patches (Saura et al, 2014), and the dispersal capacity of the species (Tscharntke et al, 2012). A functionally connected landscape is essential for maintaining healthy populations across generations because it provides access to resources, sustains metapopulations, and supports genetic diversity through gene flow (Templeton et al, 1990;Fahrig, 2003;Sodhi et al, 2011). Reductions in population size, dispersal of young individuals, and mobility of species in fragmented landscapes also alters ecological processes such as pollination and seed dispersal (Ghazoul, 2005;Magrach et al, 2014).…”
Section: Introductionmentioning
confidence: 99%